Maternal administration of flutamide during late gestation affects the brain and reproductive organs development in the rat male offspring - Pallares, Maria Eugenia (2014)
We have previously demonstrated that male rats exposed to stress during the last week of gestation present age-specific impairments of brain development. Since the organization of the fetal developing brain is subject to androgen exposure and prenatal stress was reported to disrupt perinatal testosterone surges, the aim of this research was to explore whether abnormal androgen concentrations during late gestation affects the morphology of the prefrontal cortex (PFC), hippocampus (HPC) and ventral tegmental area (VTA), three major areas that were shown to be affected by prenatal stress in our previous studies. We administered 10-mg/kg/day of the androgen receptor antagonist flutamide (4′nitro-3′-trifluoromethylsobutyranilide) or vehicle injections to pregnant rats from days 15–21 of gestation. The antiandrogenic effects of flutamide were confirmed by the analysis of androgen-dependent developmental markers: flutamide-exposed rats showed reduced anogenital distance, delay in the completion of testis descent, hypospadias, cryptorchidism and atrophied seminal vesicles. Brain morphological studies revealed that prenatal flutamide decreased the number of MAP2 (a microtubule-associated protein type 2, present almost exclusively in dendrites) immunoreactive neuronal processes in all evaluated brain areas, both in prepubertal and adult offspring, suggesting that prenatal androgen disruption induces long-term reductions of the dendritic arborization of several brain structures, affecting the normal connectivity between areas. Moreover, the number of tyrosine hydroxylase (TH)-immunopositive neurons in the VTA of prepubertal offspring was reduced in flutamide rats but reach normal values at adulthood. Our results demonstrate that the effects of prenatal flutamide on the offspring brain morphology resemble several prenatal stress effects suggesting that the mechanism of action of prenatal stress might be related to the impairment of the organizational role of androgens on brain development.